1883. Acute Kidney Injury in Patients With Pneumonia on Concomitant Anti-Methicillin-Resistant Staphylococcus aureus and Anti-Pseudomonal β-Lactam Therapy. (26th November 2018) - Raux, Brian R; Hyer, J Madison; Smith, Tiffeny T; Gnann, John W; MacVane, Shawn H
Abstract: Background: Empiric antibiotic treatment of serious and healthcare-associated pneumonia (PNA) often includes coverage of methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa (PSA). Recent publications suggest that patients treated with the combination of vancomycin (V) and piperacillin–tazobactam (PT) have a greater risk of acute kidney injury (AKI) than those treated with V alone, or V in combination with another β-lactam, such as cefepime (C). There is a paucity of data regarding the risk of AKI in other regimens that provide MRSA and PSA coverage, such as linezolid (L)-PT or LC. We examined the incidence of nephrotoxicity in patients who received combination antibiotic therapy for PNA. Methods: A retrospective cohort analysis of eligible adult patients (≥18 years) admitted from July 1, 2014 to June 30, 2017 who received ≥48 hours of combination therapy was conducted. Patients were excluded if their baseline serum creatinine was ≥1.4 mg/dL, on renal replacement therapy, or if diagnosed with cystic fibrosis. The primary outcome was incidence of AKI as defined by RIFLE criteria. Comparisons between the groups were analyzed by chi-squared test. To identify variables associated with AKI in a multivariable analysis, a repeated measures, mixed-effects logistic regression was utilized. Results: There were 185 patient encounters included in the analysis. RIFLE-defined AKI occurred in treatment groups as follows: VPT 31/98 (31.6%); VC 5/50 (10.0%); LPT 4/12 (33.3%); and LC 4/25 (16.0%). There was a significant difference in rates of AKI among the four groups ( P = 0.019). In pooled analyses, no difference was identified between patients receiving V or L ( P = 0.73); however, patients who received PT had a higher incidence of AKI compared with those that received C ( P = 0.002). In logistic regression analyses, independent predictors of AKI were receipt of PT vs. C (odds ratio [OR] 3.2, 95% confidence interval [CI] 1.3–8.0) and SOFA score ≥9 (OR, 4.5; 95% CI 1.6–12.7). Conclusion: No differences in AKI incidence were found between patients receiving vancomycin or linezolid; however, patients receiving piperacillin–tazobactam and those with SOFA scores ≥9 had a higher rate of AKI. Disclosures: All authors: No reported disclosures.